E-LearningFacultyModules.org - McHaney, Roger W.; Spire, Lynda D.; Boggs, Rosemary B. (Information Science Reference, 2013)
A team at Kansas State University recently launched the E-Learning Faculty Modules wiki to enhance and support online faculty development. This project is customized for teaching in the Kansas State University distance-learning program but contains a broad set of information that might be useful to others. This site is constructed using wiki technology, which permits access, multimedia expressiveness, remote collaboration, tracking, and reversibility of postings. Other tools on the site are derived from MediaWiki and its open-source capabilities. The wiki includes an overall ontology, templates, categories, completed and seeded entries, input boxes, and menus that ensure users can easily use and join the community. Taken holistically, these attributes create an ideal venue for sharing ideas and encouraging synergistic improvement of teaching practices. This chapter describes the implementation process of E-LearningFacultyModules.org and gives insight into its purpose, features, and uses.
Keywords: E-learning; Wikis; Online faculty development; E-Learning Faculty Modules